(untitled) (The Conference Hub, 2025)
Type 2 diabetes mellitus (T2DM) is one of the most significant global health threats, with its prevalence steadily rising worldwide. According to the International Diabetes Federation (IDF), approximately 537 million adults were living with T2DM in 2021, and this figure is projected to reach 643 million by 2030. The primary pathophysiological mechanisms of T2DM—insulin resistance and β-cell dysfunction—are closely influenced by energy balance, dietary behavior, genetic predisposition, and environmental factors.